Glucosamine mitigates ischemia-reperfusion-induced acute kidney injury through anti-inflammatory mechanisms - Zhang, Guangmin; Jin, Shengxi; Fan, Xinying; Qi, Jingjing; Liu, Jiane; Yin, Shulan; Cao, Yanjing; Du, Yiping; Dong, Xiaolei; Wang, Zheng; Tan, Xiaohua; Yan, Shu (Frontiers in Materials, 2024)
ObjectiveAcute kidney injury (AKI), a syndrome with high morbidity and mortality worldwide, frequently arises from renal ischemia-reperfusion (I/R) injury, particularly in surgical contexts. Despite extensive research, effective therapies for both AKI and its progression to renal interstitial fibrosis remain elusive. This study investigates the potential therapeutic efficacy of glucosamine (GS), an endogenous amino sugar, in alleviating I/R-induced AKI.MethodsA murine I/R injury model was utilized to evaluate the protective effects of GS. Mice were treated with GS prior to I/R injury, and renal tissues were harvested for biochemical, histological, and molecular analyses. Key markers of oxidative stress, mitochondrial integrity, and endoplasmic reticulum (ER) stress were measured. Additionally, inflammatory responses in proximal convoluted tubular epithelial cells exposed to TPHP, an environmental toxin, were assessed in vitro.ResultsGS administration markedly reduced oxidative stress levels, preserved mitochondrial structure, and mitigated ER stress in renal tissues following I/R injury. Moreover, GS significantly attenuated TPHP-induced inflammatory responses in proximal tubular epithelial cells, suggesting a targeted anti-inflammatory action.ConclusionThese findings highlight glucosamine’s potential as a therapeutic agent for AKI, offering protection through the modulation of oxidative, mitochondrial, and inflammatory pathways. This study provides foundational evidence for GS as a promising candidate for AKI intervention and opens avenues for further exploration of glucosamine in kidney disease therapeutics.